Antibacterial Activity of Two Endemic Hypericum (H. kazdaghensis and H. havvae) Against Methicillin-Resistant Staphylococcus aureus - Dulger, Gorkem; Dulger, Basaran; Aki, Cuneyt (Asian Journal of Chemistry, 2010)
Aqueous and ethanolic extracts obtained from endemic Hypericum kazdaghensis Gemici et Leblebici and H. havvae A. Guner have been investigated for its ability to inhibit 35 hospital isolated of methicillin-resistant Staphylococcus aureus (MRSA). Both aqueous and ethanolic extracts of the plant were effective on MRSA. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of the ethanolic extract with the greatest antibacterial activity were those of H. kazdagensis MIC 0.2-0.4 mg/mL and MBC 0.4-1.6 mg/ mL, respectively.